Frequency optimization and transient analyses of stiffened folded laminate composite plate using genetic algorithm - Van Binh, Bui; Ich Thinh, Tran; Minh Tu, Tran (Vietnam Journal of Science and Technology, 2017)
In  this  study,  frequency  optimization  of  stiffened  folded  laminate  composite  plate  is investigated with  respect  to  fiber orientations by using genetic algorithm  (GA). The first order shear deformation theory was used for direct frequencies calculations. The Matlab programming using rectangular isoparametric plate element with five degrees of freedom per node was built to solve  the  problems. The modulus  of  selection,  crossover  and mutation were  used  as  standard sub-modulus.  The  effects  of  obtained  optimal  fiber  orientation  on  transient  response  of  the folded plate have been investigated with difference boundary conditions. A good agreement was found between the results of this technique and other published results available in the literature.